Modification of ar-curcumene from curcuma xanthorrhiza - 271253 Ong, Pauline (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2004